Skin Barrier Recovery by Protease-Activated Receptor-2 Antagonist Lobaric Acid - Joo, Yeon Ah (Biomol Ther (Seoul), 2016)
Atopic dermatitis (AD) results from gene and environment interactions that lead to a range of immunological abnormalities and breakdown of the skin barrier. Protease-activated receptor 2 (PAR2) belongs to a family of G-protein coupled receptors and is expressed in suprabasal layers of the epidermis. PAR2 is activated by both trypsin and a specific agonist peptide, SLIGKV-NH(2) and is involved in both epidermal permeability barrier homeostasis and epithelial inflammation. In this study, we investigated the effect of lobaric acid on inflammation, keratinocyte differentiation, and recovery of the skin barrier in hairless mice. Lobaric acid blocked trypsin-induced and SLIGKV-NH(2)-induced PAR2 activation resulting in decreased mobilization of intracellular Ca(2+) in HaCaT keratinocytes. Lobaric acid reduced expression of interleukin-8 induced by SLIGKV-NH(2) and thymus and activation regulated chemokine (TARC) induced by tumor necrosis factor-a (TNF-α) and IFN-γ in HaCaT keratinocytes. Lobaric acid also blocked SLIGKV-NH(2)-induced activation of ERK, which is a downstream signal of PAR2 in normal human keratinocytes (NHEKs). Treatment with SLIGKV-NH(2) downregulated expression of involucrin, a differentiation marker protein in HaCaT keratinocytes, and upregulated expression of involucrin, transglutamase1 and filaggrin in NHEKs. However, lobaric acid antagonized the effect of SLIGKV-NH(2) in HaCaT keratinocytes and NHEKs. Topical application of lobaric acid accelerated barrier recovery kinetics in a SKH-1 hairless mouse model. These results suggested that lobaric acid is a PAR2 antagonist and could be a possible therapeutic agent for atopic dermatitis.